The relationship between ethical leadership, moral sensitivity, and moral courage among head nurses - Juntong Meng; Xiaoling Guo (BMC Nursing)
Abstract Background Moral courage is a key factor in accelerating the implementation of moral behavior. Effective ethical leadership can enhance head nurses’ moral competence—particularly moral sensitivity, which serves as a cornerstone of the moral decision-making process. However, there is limited evidence on how ethical leadership influences moral courage. This study aimed to examine the mediating role of moral sensitivity in the relationship between ethical leadership and moral courage among head nurses in China. Methods A cross-sectional study was conducted between April and May 2024. The study sample consisted of 202 head nurses who agreed to participate in the study. Data were collected using the Ethical Leadership Scale, the Moral Sensitivity Scale, and the Moral Courage Scale. Results A total of 212 head nurses participated in this study. The total scores of ethical leadership, moral sensitivity and moral courage of Chinese head nurses were 92.66(16.34), 45.05(6.40) and 84.64(14.84), respectively. Ethical leadership was positively correlated with moral sensitivity (r = 0.16, P < 0.05), ethical leadership was positively correlated with moral courage (r = 0.32, P < 0.01), and moral sensitivity was positively correlated with moral courage (r = 0.31, P < 0.01). Process analysis showed that ethical leadership enhanced the moral courage of head nurses through moral sensitivity, which was a partial mediating effect model, and the total indirect effect accounted for 13.79%. Conclusions This study demonstrates that ethical leadership significantly enhances head nurses’ moral sensitivity and courage, with moral sensitivity serving as a critical mediating factor. The study reveals a cascade effect: the moral quality of senior managers shapes the ethical standards of head nurses, and then affects the behavior of clinical nurses, and ultimately forms the ethical organizational culture. Clinical trial number Not applicable.